The empowerment of national naval shipbuilding industry: a systematic literature review of water-based defence capabilities between Malaysia and South Korea - Abdul Muein Abadi; Suziana Samin; Mohd Firdaus Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2024)
The development of a robust naval shipbuilding industry is pivotal for national defense and economic advancement. Malaysia and South Korea, despite their differing industrial trajectories, provide valuable comparative insights into the empowerment of national naval shipbuilding capabilities. This study examines the strategies, challenges, and outcomes of naval shipbuilding in these two countries, focusing on their policy frameworks, technological advancements, and domestic industrial participation. Using a systematic literature review methodology, the research synthesizes findings from peer-reviewed journals, government reports, and industry analyses to identify patterns and divergences. The objectives are: i. To analyse the factors that are likely to prevent self-reliance in Malaysia’s naval shipbuilding industry; ii. To analyse the weaknesses and challenges of Malaysia Defence Policy applied in the national naval shipbuilding industry; iii. To review South Korea’s policies and analyse the strengths and weaknesses of its applied defense policy in supporting their naval shipbuilding industry.; iv. To recommend the strategies and policies enhancement to improve the National Naval Shipbuilding Industry. The findings reveal that South Korea’s success lies in its comprehensive industrial ecosystem, supported by state-driven initiatives and technological investments, enabling it to become a global shipbuilding leader. In contrast, Malaysia faces significant barriers, including limited technological capacity, dependency on foreign expertise, and inconsistent policy execution, which hinder its potential growth. The study underscores the need for Malaysia to adopt a more cohesive approach, emphasizing technology transfer, workforce development, and sustained policy commitment. By identifying best practices from South Korea, this research offers policy recommendations aimed at strengthening Malaysia’s naval shipbuilding industry and enhancing its strategic autonomy. The comparative analysis contributes to the broader discourse on the intersection of defense industrialization and national development.